2020
DOI: 10.1111/beer.12265
|View full text |Cite
|
Sign up to set email alerts
|

Does context matter for sustainability disclosure? Institutional factors in Southeast Asia

Abstract: Corporate sustainability is a dynamic, socially constructed concept. Relatedly, to understand the variations in the disclosure of corporate sustainability activities across countries, we need to inherently explore their underlying sociopolitical contexts. At present our understanding in this regard, is deficient. We respond to this extant research gap by adopting a multi‐country approach to investigate the relationship between countries' institutional environments and firms' sustainability disclosure (SD) prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 162 publications
(268 reference statements)
2
49
1
7
Order By: Relevance
“…In addition, the NBS highlights the influence of national philanthropic culture on CSR practices (Matten & Moon, 2008). Tran and Beddewela (2020) found that differences in culture led to significant differences in CSR reporting and practices in six countries in the Southeast Asian region. In societies where “giving back to society” is highly regarded, corporations that fail to live up to this cultural norm may face social condemnation (Matten & Moon, 2008).…”
Section: Institutional Influence and Nbs Theorymentioning
confidence: 99%
“…In addition, the NBS highlights the influence of national philanthropic culture on CSR practices (Matten & Moon, 2008). Tran and Beddewela (2020) found that differences in culture led to significant differences in CSR reporting and practices in six countries in the Southeast Asian region. In societies where “giving back to society” is highly regarded, corporations that fail to live up to this cultural norm may face social condemnation (Matten & Moon, 2008).…”
Section: Institutional Influence and Nbs Theorymentioning
confidence: 99%
“…Companies disclose either as a response to perceived legitimacy threats (Woo, Jung, & Jin, 2020) or as a means to maintain legitimacy among stakeholders (Cormier & Magnan, 2015). The main bulk of the literature on non-financial disclosure concerns diverse determinants of disclosure (Kraft, 2018), such as the role of context (Tran & Beddewela, 2020). Second, there is research providing direction on the impact disclosure has on legitimacy (Cormier & Magnan, 2015) and on financial performance (Lawal, May, & Stahl, 2017).…”
mentioning
confidence: 99%
“…In view of the contradiction and conflict between socioeconomic development and the natural ecosystem (Lu et al, 2020;Shan & Duchi, 2020;Solonenko, 2019), such ideas as sustainable development, circular economy, and smart growth have become the core of current environmental issues (Barbesgaard, 2017;Rodr ıguez et al, 2020;Thomas & Littlewood, 2010;Tran & Beddewela, 2020;Villate et al, 2020). Green infrastructure, as an effective method to coordinate environmental, social, and economic development, has become one of the important strategies to achieve sustainable development (Ahern, 2011;Apostolopoulou & Adams, 2015;Cortinovis & Geneletti, 2018;De Valck et al, 2019).…”
Section: Introductionmentioning
confidence: 99%